PERAN FIQIH MUNAKAHAT DALAM PERNIKAHAN MUSLIM: PANDUAN UNTUK KEHIDUPAN BERUMAH TANGGA YANG BAHAGIA - hasbi ashiddiqi, mohammad; Dermawan, Naufal (Muadalah : Jurnal Hukum, 2023)
Humans are living creatures who have instincts and desires. Marriage is one of a person's instincts and obligations. In fact, Islam has provided guidance to those who will enter the marriage stage, complete with the procedures or rules of Allah SWT. So those who are considered experts in worship do not choose alternative methods. All living creatures have the desire to reproduce and pass on their genetic makeup, but marriage is what differentiates humans from other animals. Allah SWT encourages people to marry in order to maintain their existence and regulate reproduction in a socially acceptable way. Religion has become human nature if men and women need each other. The problem formulation in this research is what is the role of munakahat fiqh in Muslim marriages so that life in the household is happy. This research is qualitative research with a multiple literature review approach. The aim of this research is to find out the role of munakahat fiqh in Muslim marriages so that life in the household is happy.